1992
DOI: 10.1128/aac.36.6.1208
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interactions of biofilms of mucoid Pseudomonas aeruginosa with tobramycin and piperacillin

Abstract: The dynamic interaction of planktonic and biofilm cells of mucoid Pseudononas aeruginosa with tobramycin and piperacillin was investigated in a chemostat system. The results indicated that planktonic and young biofilm cells of the 2-day-old chemostat culture of P. aeruginosa were susceptible to killing by chemostatcontrolled doses of either 250 ,ug of piperacillin per ml plus 5 ,ug of tobramycin per ml or 500 ,ug of piperacillin per ml plus 5 jig of tobramycin per ml. Complete eradication of the planktonic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 29 publications
4
67
0
Order By: Relevance
“…However, the effect of alginate overproduction on P. aeruginosa biofilm formation remains undetermined. Some reports have suggested that mucoid P. aeruginosa biofilms are more resistant to antibiotics than nonmucoid biofilms (2,35). However, these studies were limited in that the strains used for comparison were not isogenic derivatives.…”
mentioning
confidence: 99%
“…However, the effect of alginate overproduction on P. aeruginosa biofilm formation remains undetermined. Some reports have suggested that mucoid P. aeruginosa biofilms are more resistant to antibiotics than nonmucoid biofilms (2,35). However, these studies were limited in that the strains used for comparison were not isogenic derivatives.…”
mentioning
confidence: 99%
“…Once established, the chronic P. aeruginosa lung infection tolerates the highest deliverable doses of antibiotics (Anwar et al, 1992) and cannot be eradicated (Koch & Hoiby, 1993). The inflammatory response to the chronic infection is mainly characterized by the constant influx of polymorphonuclear leukocytes (PMNs), which surround the bacteria (Baltimore et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…More recent evidence suggests a contribution of the biofilm physiology to tolerance, as biofilm bacteria are physiologically distinct from planktonic bacteria, expressing specific protective factors, such as multidrug (MDR) efflux pumps and stress response regulons (6,7,9,10,13,(22)(23)(24)(25). Moreover, bacteria within microbial communities were found to employ a specific regulatory mechanism to resist the action of antimicrobial agents.…”
mentioning
confidence: 99%
“…This enhanced tolerance is thought to be multifactorial, requiring a combination of different mechanisms, and is distinct from mechanisms more commonly associated with planktonic cells, such as acquisition of resistance through random mutation or uptake of plasmid-borne resistance markers (6)(7)(8)(9)(10)(11). Mechanisms contributing to high antimicrobial tolerance in biofilms are thought to include reduced metabolic and growth rates (12)(13)(14), the presence of dormant persister cells that are not killed by exposure to antibiotics (15), restricted diffusion of certain types of antimicrobial agents (11,16,17), starvation-induced growth arrest (18), and the maturity or developmental stage of the biofilm (13,19). The notion of multifactorial mechanisms contributing to biofilm tolerance is supported by several observations.…”
mentioning
confidence: 99%